2020
DOI: 10.2147/opth.s264370
|View full text |Cite
|
Sign up to set email alerts
|

<p>Outcomes of Femtosecond Laser Arcuate Incisions in the Treatment of Low Corneal Astigmatism</p>

Abstract: To evaluate real-world outcomes of astigmatism management with femtosecond laser arcuate incisions in patients with low corneal astigmatism (<1.0 D) using a novel formula for arcuate incision calculation compared to outcomes after conventional cataract surgery without surgical management of astigmatism. Patients and Methods: The Wörtz-Gupta™ Formula (available at www.lricalc.com) was used to calculate femtosecond laser arcuate parameters for 224 patients with <1 D of corneal astigmatism who underwent cataract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…However, the overcorrection rates did not significantly differ between the groups ( p = 0.643). In another study, the authors reported that, in patients with a relatively lower degree of corneal astigmatism, FL-AK outcomes were influenced by preoperative corneal astigmatism and uncorrected visual acuity ( 18 ). The authors of that study utilized a novel formula to reduce the corneal incision arc by 20–30%, and the novel formula was more effective in correcting low astigmatism than the pre-existing method.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overcorrection rates did not significantly differ between the groups ( p = 0.643). In another study, the authors reported that, in patients with a relatively lower degree of corneal astigmatism, FL-AK outcomes were influenced by preoperative corneal astigmatism and uncorrected visual acuity ( 18 ). The authors of that study utilized a novel formula to reduce the corneal incision arc by 20–30%, and the novel formula was more effective in correcting low astigmatism than the pre-existing method.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that more recent, advanced nomograms/formulas could further improve mean results or reduce outcome variability. 15 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Mean results achieved can be similar to those reported here, but in general there is more variability in the outcomes with corneal incisions relative to toric IOLs, particularly when the incisions are made with a blade. 8 Other studies have found that femtosecond LRIs can provide results similar to a toric IOL, [14][15][16] but several authors have noted that the additional surgical time requirement, incision planning and laser system cost might argue for toric IOL use. A meta-analysis of studies that included LRIs made with both manual and femtosecond laser systems suggests that the likelihood of achieving a residual refractive cylinder of ≤0.50 D is higher with a toric IOL.…”
Section: Discussionmentioning
confidence: 99%